Decentralized procurement practice at municipality level under BMDF financing in Bangladesh: an analysis - Hossain, Mohammad Ali (BRAC University, 2014)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2014.